Effects of Illustration in Online Banner: an Eye Tracking Study Among Food Service Advertisement - Eddy Yansen; Kevin Krisma Joanito Gea; L Mutiara C Pangestu; Prima Setyaningrum; Tri Liniarti (Co-Value Jurnal Ekonomi Koperasi dan kewirausahaan, 2023)
This research investigates the influence of gender, age, and Area of Interest (AOI) layout on the efficacy of food advertisement banners employed by a food delivery service company within the digital marketing landscape. As technology continues to advance, companies are increasingly adopting digital marketing strategies to promote their products and services. The study utilized a quantitative research approach and was conducted online, involving a sample of 20 individuals who regularly use the food delivery service application, GoFood. A random sampling technique was employed, and data collection was facilitated through the application of eye-tracking methodology, utilizing the Gaze Recorder application. Subsequently, dwell time data were subjected to rigorous statistical analysis using Two-Way Analysis of Variance (ANOVA). The outcomes of this study yielded several notable findings: Gender was identified as a significant factor impacting dwell time, resulting in variations in residence time on the two distinct banner advertisements, Age was also found to exert a discernible influence on dwell time, contributing to disparities in residence time across the two banner ads, Additionally, when scrutinizing residence time from the vantage point of AOI layout, as determined through heatmap analysis, discernible differences were observed in residence time for the two advertising banners. This research underscores the pivotal roles played by gender, age, and AOI layout in shaping the effectiveness of food advertisement banners within the digital marketing strategies of food delivery service companies. These findings provide valuable insights for marketers seeking to optimize their digital advertising campaigns to cater to diverse demographic segments